2020
DOI: 10.1080/1343943x.2020.1758171
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal changes in chloroplast positioning and photosynthetic traits of C4 grass finger millet

Abstract: Mesophyll (M) chloroplasts in finger millet are known to aggregate to the bundle sheath side when leaves are constantly irradiated with extremely high-intensity light. This aggregative movement of M chloroplasts is also observed in natural environment, but whether a natural light regime is effective in inducing the response remains unclear. Abscisic acid is reported to trigger not only the aggregative movement but also stomatal closure, but photosynthetic responses accompanying the aggregative movement also re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 51 publications
2
20
0
Order By: Relevance
“…Chloroplast arrangements differ depending on species, light quality and intensity. For instance, under midday illumination Eleusine coracana was shown to aggregate M chloroplasts around the BS; Zea mays showed a dispersed arrangement, similar to what we observed in S. viridis ; Sorghum bicolor created characteristic optical corridors spanning the whole leaf thickness, presumably aiding photoprotection, observed also in Z. mays but only under non–physiological irradiance (3,000–4,000 μmol m -2 s -1 ) (Yamada et al , 2009, Maai et al , 2020a, Maai et al , 2020b). Secondly, in LL leaves the BS had higher chlorophyll content (Table 1) and increased abundance of light-harvesting complexes (LHC) I and II compared to HL plants (Ermakova et al , 2021b).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Chloroplast arrangements differ depending on species, light quality and intensity. For instance, under midday illumination Eleusine coracana was shown to aggregate M chloroplasts around the BS; Zea mays showed a dispersed arrangement, similar to what we observed in S. viridis ; Sorghum bicolor created characteristic optical corridors spanning the whole leaf thickness, presumably aiding photoprotection, observed also in Z. mays but only under non–physiological irradiance (3,000–4,000 μmol m -2 s -1 ) (Yamada et al , 2009, Maai et al , 2020a, Maai et al , 2020b). Secondly, in LL leaves the BS had higher chlorophyll content (Table 1) and increased abundance of light-harvesting complexes (LHC) I and II compared to HL plants (Ermakova et al , 2021b).…”
Section: Discussionsupporting
confidence: 77%
“…Firstly, the arrangement of M chloroplasts appressed to the cell walls (Figure 1), similar to that observed in Saccharum officinarum grown under low light (Sales et al, 2018), created optical gaps, increasing the amount of light filtering through to BS cells, a phenomenon known as the 'sieve effect' (Terashima et al, 2009), while in HL plants M chloroplasts were dispersed. Rapid movement of M chloroplasts in response to HL is mediated by a blue light receptor and influenced by the presence of abscisic acid but not by the circadian clock (Maai et al, 2020a (Yamada et al, 2009, Maai et al, 2020a, Maai et al, 2020b. Secondly, the BS had higher chlorophyll content (Table 1), lower chlorophyll a/b ratio and higher abundance of light-harvesting complexes (LHC) I and II than HL plants (Ermakova et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Chloroplast arrangements differ depending on the species and the light quality and intensity. For instance, under midday illumination: Eleusine coracana was shown to aggregate M chloroplasts around the BS; Zea mays showed a dispersed arrangement, similar to that observed in S. viridis ; and Sorghum bicolor created characteristic optical corridors spanning the whole leaf thickness, presumably aiding photoprotection, which was also observed in Z. mays but only under non‐physiological irradiance (3000–4000 μmol m −2 sec −1 ) (Maai et al., 2020a, 2020b; Yamada et al., 2009). Second, in LL leaves the BS had higher chlorophyll content (Table 1) and increased abundance of light‐harvesting complexes (LHC) I and II, compared with HL plants (Ermakova, Bellasio, et al., 2021).…”
Section: Discussionmentioning
confidence: 83%
“…Since ACS-430 is an active sensor that has its own light source, the impact of changes in solar angle at different times of a day was assumed to be small, although Kim et al (2012) observed some changes in canopy reflectance within a day. In addition, we assumed that the effects of changes in diurnal leaf movement ( Wang et al, 2004 ; Greenham et al, 2015 ; Cal et al, 2018 ), leaf area shrinkage ( Hilty, Pook & Leuzinger, 2009 ; Dong et al, 2011 ), as well as chlorophyll positioning ( Maai et al, 2020 ), were minimum to our measured values of NDVI, and the key signals captured by our active spectral sensor, which was consistently positioned at a common height on the sensing frame looking down vertically at the plant canopy, originated mainly from the changes in leaf water status of the closed canopies of wheat, corn or cotton. We noted a moderate correlation between air temperature and NDVI for the combined corn/cotton samples (R 2 = 0.21; see Fig.…”
Section: Discussionmentioning
confidence: 99%